Increased renal DNA synthesis in vivo after administration of low doses of gentamicin to rats. - Laurent, G (1983)
Kidney cortex DNA synthesis was studied in female rats treated with a low dose of gentamicin (10 mg/kg) up to 14 days. Synthesis was measured by incorporation of [3H]thymidine into DNA 1 h after intraperitoneal injection of the labeled precursor (200 muCi per animal). Gentamicin given in one injection per day resulted in a greater incorporation of [3H]thymidine into DNA after both 7 and 14 days of treatment as compared with control animals. When the daily dose was divided into three equal injections given at 8-h intervals, a statistically significant increase in thymidine incorporation was observed as early as 4 days after starting gentamicin administration. Excellent agreement was found between DNA specific radioactivity and kidney cortex nuclear labeling, as measured by histoautoradiography. The greatest amount of [3H]thymidine incorporation occurred within proximal tubular cells and interstitial cells. We conclude that a finite duration of gentamicin treatment at low dosage induces an increased DNA synthesis in vivo in rat kidney cortex. We suggest that this reaction results from cellular proliferation and could reflect a regenerative process after focal necrosis induced by gentamicin at low doses. The demonstrated early increase in DNA synthesis could be a useful tool to measure kidney cortex alterations caused by various aminoglycosides at low, therapeutic doses.